2005
DOI: 10.1016/j.jom.2005.05.003
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of ‘close’ supplier–manufacturer relationships

Abstract: Close relationships with selected suppliers can enable manufacturers to reduce costs, improve quality and enhance new product development. Although the advantages of close co-operation are widely acknowledged in the literature, the specific attributes of such relationships are not well understood. To address this gap, 39 managers responsible for purchasing were interviewed using a technique from psychology, which is particularly effective at uncovering the characteristics of relationships. This approach is inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
270
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(291 citation statements)
references
References 44 publications
7
270
0
2
Order By: Relevance
“…(Goffin et al, 2006). This can be explained by the lack of qualitative theory building research on the topic (Handfield and Melnyk, 1998) and hence the necessity for more exploratory research that proposes models and frameworks that can be further tested and modified (Burgess et al, 2006;Olsen and Ellram, 1997a).…”
Section: Unit Of Analysismentioning
confidence: 99%
“…(Goffin et al, 2006). This can be explained by the lack of qualitative theory building research on the topic (Handfield and Melnyk, 1998) and hence the necessity for more exploratory research that proposes models and frameworks that can be further tested and modified (Burgess et al, 2006;Olsen and Ellram, 1997a).…”
Section: Unit Of Analysismentioning
confidence: 99%
“…However, in the area of supply chain relationships where customers are defined as the next member of supply chain, these relationships are transformed into B2B partnership-like nature as a result of co-creation. Goffin et al (2006) point to several important literature implications of these relationships; advantages including better quality, lower costs and reliable delivery. Instead of competing, members of a supply chain can expand the value as well as their share from the pie through the co-creation processes as shown in Figure 1.…”
Section: H1: Entrepreneurship Orientation Positively Affects Co-creatmentioning
confidence: 98%
“…Whereas some argue that close relationships are beneficial (Goffin, Lemke, & Szwejczewski, 2006), and others warn of their downsides (Erin & Sandy, 2005). While the two aforementioned paper views offer solid justification for their diametrically opposed positions, the authors still agree on the importance of those relationships and on which degree of closeness should be sought.…”
Section: Background On Scm and Supplier Relationshipmentioning
confidence: 99%
“…While no papers directly relating to supplier relationships within the cruise industry were found, interesting elements from other sectors were explored and tested within the cruise supply chain paradigm. Some elements that were recently validated in a study by Goffin et al (2006) include the following: commitment, delivery performance, joint problem solving, and long-term vision. Overall, it was found that there remains a paucity of research on specific attributes of close successful relationships and extant research calls for more study on the matter.…”
Section: Background On Scm and Supplier Relationshipmentioning
confidence: 99%